The subject matter of intellectual property - Pila, Justine (Oxford : Oxford University Press, 2017)
A clear and practical guide to the categories of subject matter protected by the main Intellectual Property regimes, focusing on their constitutive aspects and differences.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 16, 2017).
Keywords: Intellectual property; Law; Laws of specific jurisdictions & specific areas of law